Behavioral Economics and the Public Acceptance of Synthetic Biology - Oliver, Adam (The Hastings Center report, 2018)
Different applications of synthetic biology are alike in that their possible negative consequences are highly uncertain, potentially catastrophic, and perhaps irreversible; therefore, they are also alike in that public attitudes about them are fertile ground for behavioral economic phenomena. Findings from behavioral economics suggest that people may not respond to such applications according to the normal rules of economic evaluation, by which the value of an outcome is multiplied by the mathematical probability that the outcome will occur. Possibly, then, synthetic biology applications challenge the normative postulates of the standard approach, too. I want to first consider how some of the phenomena described by behavioral economists—and behavioral scientists more broadly—might affect people's perceptions of the uncertainties associated with synthetic biology. My analysis will be far from complete, however, because behavioral economics is essentially the study of human behavior, and thus its reach is potentially vast and its development longstanding and ongoing. Nonetheless, I hope to give an indicative perspective on how some aspects of behavioral economics might affect the assessment and perceived acceptability of synthetic biology. I will then consider the issue of agency. Should policy-makers respect people's reactions to synthetic biology when those reactions are known to be driven by behavioral economic phenomena rather than following the normative postulates of rational choice theory? Or should policy-makers dismiss these reactions as inherently biased? I will argue that the normative force of these human reactions (probably) depends on phenomenon and context.